Preparation method of modified cerium-zirconium solid solution

By doping alkaline earth metal magnesium and strontium into the cerium-zirconium solid solution and using specific dispersants and surfactants, the modified cerium-zirconium solid solution is solved, and the problem of taking into account both oxygen storage/oxygen release rate and capacity in the prior art is improved, and its treatment efficiency for automobile exhaust pollutants is improved.

CN119346098BActive Publication Date: 2025-03-25ZIBO JIAHUA ADVANCED MATERIAL RESOURCES CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411933166.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-25
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

While the existing cerium-zirconium solid solution increases the oxygen storage/oxygen release rate, it is difficult to take into account the problem of high oxygen storage capacity, resulting in low efficiency in dealing with pollutants in automobile exhaust.

Method used

Modified cerium-zirconium solid solution was prepared by doping alkaline earth metal magnesium and strontium into the cerium-zirconium solid solution, and using a mixture of gallic acid, lauric acid and stearamine as the dispersant, and using surfactant as the component of the template solution to control the precipitation reaction and roasting process.

Benefits of technology

While cerium-zirconium solid solution has high oxygen storage capacity, it has increased the oxygen storage/oxygen release rate, enhanced its ability to deal with pollutants in automobile exhaust, and met the technical requirements of the existing three-effect catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention belongs to the technical field of metal oxides, and specifically relates to a method for preparing a modified cerium-zirconium solid solution. The preparation method comprises the following steps: adding cerium salt, zirconium salt, rare earth metal salt and alkaline earth metal salt to a surfactant solution to prepare a template solution; preparing a precipitant by adding ammonia water and a dispersant; stirring and aging the template solution and the precipitant, and washing and roasting the precipitate obtained after aging to prepare a modified cerium-zirconium solid solution. The modified cerium-zirconium solid solution prepared by the present invention has a large oxygen storage capacity and solves the problem of insufficient oxygen storage / oxygen release performance of the existing doped and modified cerium-zirconium solid solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal oxides, and particularly relates to a preparation method of a modified cerium-zirconium solid solution. Background Art

[0002] Automobile exhaust emissions are one of the main sources of air pollution, including carbon monoxide (CO), hydrocarbons (HC), nitrogen oxides (NO X ) and other pollutants. The common prevention and control measures at present are to install a three-way catalyst in the automobile exhaust system to capture pollutants and convert the captured pollutants into carbon dioxide, water and nitrogen through redox reactions. Due to the complexity of the engine operating conditions, its air-fuel ratio changes periodically. After deviating from the ideal air-fuel ratio, the three-way catalyst is less effective for CO, HC and NO. X There is a big difference in the catalytic performance of the three-way catalyst, so the technicians added cerium zirconium solid solution (CeO 2 -ZrO 2 ) as an oxygen storage-oxygen release material to narrow and stabilize the three-way window near the ideal air-fuel ratio, thereby improving the treatment efficiency of all pollutants. Therefore, the strength of oxygen storage and oxygen release performance directly determines whether the three-way catalytic performance can be further improved.

[0003] Because the engine is in the instantaneous acceleration condition, carbon monoxide, hydrocarbons, nitrogen oxides and other pollutants are generated in large quantities in an instant, which are easy to break through the capture of the three-way catalyst and overflow into the atmosphere. With the increasingly stringent automobile emission standards, the simple cerium-zirconium solid solution is difficult to meet the current emission standards, especially the unmodified cerium-zirconium solid solution has a contradiction: the research found that the increase of Zr content will reduce Ce 4+ →Ce 3+ The reduction reaction energy barrier of Ce can reduce the activation energy of oxygen ion migration in the lattice, thereby increasing the oxygen storage / release rate; however, Ce 3+ and Ce 4+ The content of Zr directly determines the size of the oxygen storage capacity. An increase in the Zr content means a relative decrease in the Ce content, which will lead to a relative decrease in the oxygen storage capacity. How to improve the cerium-zirconium solid solution by optimizing the preparation process, doping modification or crystal structure regulation to overcome this contradiction as much as possible is one of the main research topics of current technicians.

[0004] Chinese patent CN104492414A discloses a method for preparing a cerium-zirconium solid solution. The steps of the preparation method are as follows: (1) preparing Ce 4+ Clarify solution A; (2) to Ce 4+The method comprises the following steps: (1) adding nitrates of rare earth oxides other than cerium and zirconium oxynitrate to a clear solution A, and adding an organic complexing agent to obtain an active component solution B; (2) subjecting the active component solution B to a precipitation reaction to obtain a solid-liquid mixed slurry C; (3) adding polyacrylic acid to the solid-liquid mixed slurry C for surface modification to obtain a material D; and (4) calcining the material D to obtain a cerium-zirconium solid solution. The organic complexing agent is a hydroxycarboxylic acid compound, and the hydroxycarboxylic acid compound is one or two of α-hydroxyisobutyric acid, lactic acid, and α-hydroxyacetic acid.

[0005] According to the patent description, the organic complexing agent used controls the speed of the precipitation reaction and improves the solid solubility of rare earth ions and zirconium ions; polyacrylic acid reduces the agglomeration of particles during calcination and ensures that the cerium-zirconium-based solid solution has good thermal stability. However, it does not specifically address the issue of how to make the cerium-zirconium solid solution take into account both high oxygen storage / oxygen release rate and high oxygen storage capacity.

[0006] Chinese patent CN105642269A discloses a composite cerium-zirconium solid solution and a preparation method thereof, wherein the composite cerium-zirconium solid solution is composed of cerium oxide, zirconium oxide and rare earth additives, wherein by mass, cerium oxide accounts for 15-80%, zirconium oxide accounts for 15-60%, and rare earth additives account for 5-25%; wherein the rare earth additives are one or more of lanthanum oxide, praseodymium oxide, rubidium oxide, yttrium oxide, samarium oxide, terbium oxide, dysprosium oxide, and erbium oxide. The preparation method is to prepare cerium carbonate, zirconium carbonate and rare earth additives into a nitrate mixed solution A; prepare a surfactant into a solution B; and finally prepare the composite cerium-zirconium solid solution using the nitrate mixed solution A and the solution B. The surfactant is a mixture of fatty acid or carboxylic acid ester and alcohol polymer, wherein the fatty acid is one or more of lauric acid, palmitic acid, stearic acid, and oleic acid; the carboxylic acid ester is one or more of Tween 20, Tween 60, and Tween 80; and the alcohol polymer is polyvinyl alcohol or polyethylene glycol.

[0007] Surfactants are added in this patent; it is generally believed that when the coprecipitation method is used, the surfactant plays a role in stabilizing dispersion and reducing agglomeration, thereby ultimately increasing the specific surface area of ​​the cerium-zirconium solid solution. Examples 1-4 of the patent specification mention that the oxygen storage capacity of the cerium-zirconium solid solution is good, but it does not specifically address the issue of how to make the cerium-zirconium solid solution have both high oxygen storage / oxygen release rate and high oxygen storage capacity.

[0008] The existing patents focus on improving the specific surface area, oxygen storage capacity and anti-aging ability of cerium-zirconium solid solution. In particular, oxygen storage capacity (also known as oxygen storage capacity) only reflects the amount of oxygen vacancies generated, but the generation and migration rate of oxygen vacancies, that is, the oxygen storage / oxygen release rate, is equally important for the ability to capture pollutants in automobile exhaust. It can be found that the existing technology does not pay enough attention to how to make cerium-zirconium solid solution take into account both high oxygen storage / oxygen release rate and high oxygen storage capacity. Summary of the invention

[0009] The object of the present invention is to provide a method for preparing a modified cerium-zirconium solid solution, which has a high oxygen storage capacity and solves the problem of insufficient oxygen storage / oxygen release performance of the existing doped-modified cerium-zirconium solid solution.

[0010] To achieve the above object, the technical solution adopted by the present invention is:

[0011] The preparation method of the modified cerium-zirconium solid solution of the present invention comprises the following steps: adding cerium salt, zirconium salt, rare earth metal salt and alkaline earth metal salt into a surfactant solution to prepare a template liquid; preparing a precipitant by adding ammonia water and a dispersant; stirring and aging the template liquid and the precipitant, washing and calcining the precipitate obtained after aging to prepare the modified cerium-zirconium solid solution.

[0012] in:

[0013] The cerium salt is cerous nitrate; the zirconium salt is zirconyl nitrate; the rare earth metal salt is one or more of praseodymium nitrate, lanthanum nitrate, yttrium nitrate or neodymium nitrate; and the alkaline earth metal salt is strontium nitrate and magnesium nitrate.

[0014] Taking the total molar number of the four types of metal salts as 100%, cerium salts account for 40-50%, zirconium salts account for 35-40%, rare earth metal salts account for 9-11%, and alkaline earth metal salts account for 6-10%; the molar ratio of strontium nitrate to magnesium nitrate is 1:(0.8-1).

[0015] Taking the total molar number of the four types of metal salts as 100%, the cerium metal salt accounts for 40%, the zirconium metal salt accounts for 40%, the lanthanum nitrate accounts for 5%, the yttrium nitrate accounts for 5%, the strontium nitrate accounts for 5%, and the magnesium nitrate accounts for 5%.

[0016] The surfactant solution is prepared by blending a surfactant, a surfactant auxiliary and an organic solvent, wherein the surfactant is one of dodecyldimethylbenzyl ammonium chloride, dodecylpyridinium ammonium chloride or hexadecyltrimethylammonium chloride; the surfactant auxiliary is n-hexanol; the organic solvent is one of chloroform, ether or acetone; and the volume ratio of the surfactant, the surfactant auxiliary and the organic solvent is 1:1:(3-5).

[0017] The ratio of the added amount of the four types of metal salts to the surfactant solution is 1: (0.6~0.9), wherein the four types of metal salts are the total molar number, measured in mol, and the surfactant solution is measured in L; the molar ratio of the total amount of cerium salt and zirconium salt to the added amount of ammonia water is 1: (1.1~1.35).

[0018] The dispersant is a mixture of gallic acid, lauric acid and stearylamine, the molar ratio of gallic acid, lauric acid and stearylamine is 1:1:(2-10); the molar ratio of the dispersant to the total molar number of the four types of metal salts is (0.8-1):1.

[0019] During the aging, the pH is controlled at 9.5-10.5, the aging time is 1-2 hours, and the aging temperature is 55-65°C.

[0020] The stirring rate is 500-800 rad / min; the conductivity of the washed precipitate is ≤30 mS / cm.

[0021] The calcination temperature is 800-900°C, and the calcination time is 6-8h.

[0022] The beneficial effects of the present invention are as follows:

[0023] (1) Doping alkaline earth metals magnesium and strontium into cerium-zirconium solid solution:

[0024] The mechanism of action of cerium-zirconium solid solution: Under the operating conditions of the engine, the air-fuel ratio will fluctuate above and below the ideal air-fuel ratio. At this time, the exhaust gas discharged from the car will be in oxygen-rich and oxygen-poor states respectively. When oxygen is rich, oxygen will Ce 3+ Oxidized to Ce 4+ The oxygen ions formed will react with other cations (such as Zr 4+ ) forms a stable structure and forms equivalent oxygen vacancies. At this time, the oxygen vacancies tend to move to the surface under the action of energy potential difference; when oxygen is deficient, pollutants such as carbon monoxide and hydrocarbons will Ce 4+ Restore to Ce 3+ , it will be converted into carbon dioxide and water, and oxygen vacancies will be formed at the same time. At this time, the oxygen vacancies will tend to move to the bulk phase under the action of energy potential difference. Therefore, the speed of oxygen vacancy generation and migration rate is manifested as the strength of oxygen storage / release capacity on a macro scale.

[0025] The microscopic mechanisms of insufficient oxygen storage / release capacity are mainly: 1. The lattice structure is tight and the coordination number is stable, resulting in a high energy barrier for oxygen vacancy migration; 2. During high-temperature calcination, ions migrate due to activation, which makes the lattice ordered, reduces oxygen vacancies, and increases the energy barrier for oxygen vacancy migration; 3. Metastable phase decomposition. Due to the uneven distribution of Ce-Zr, a metastable phase exists at the interface of the thermodynamically stable cubic phase. High temperature provides migration activation energy for ions in the non-stable metastable phase, resulting in the formation of a Zr-rich tetragonal phase at the interface of the Ce-rich cubic phase. Since the tetragonal phase has a tighter structure, it will cause an increase in the energy barrier for oxygen vacancy migration.

[0026] Doping with alkaline earth metals, preferably strontium and magnesium: by doping with a reasonable amount of magnesium (ionic radius of 0.066nm), replacing the original position of Zr with a larger ionic radius 4+ (0.084nm) and Ce 4+ (0.097nm), which reduces the density of cubic fluorite lattice structure, thereby reducing the steric hindrance of oxygen ion migration; with the Ce 4+ (0.097nm) to Ce 3+ (0.114nm) transformation, the crystal volume expansion produces structural stress, which inhibits the Ce 4+ The further transformation of Ce by doping with Mg helps Zr to further compensate for the volume expansion effect of Ce transformation and promotes Ce 4+ To Ce 3+ transformation, and also enhanced the rate of oxygen vacancy generation and migration; and magnesium in CeO 2 The activation energy of migration in the lattice is lower than that of Zr, which inhibits the ordering of the lattice due to ion rearrangement during high-temperature calcination. On the other hand, magnesium doping causes lattice distortion, reducing Zr 4+ The coordination number of adjacent oxygen increases the oxygen vacancy concentration, that is, the oxygen storage capacity is increased; in addition, the difference between the magnesium ion radius and the Zr ion radius is less than but close to 30%, avoiding the phenomenon of reduced solid solubility and phase separation. And affect the mechanical strength of the material. By doping a reasonable amount of strontium (ion radius is 0.11nm), the ion radius is not much different, it can fully replace the original position of Ce and Zr, improve the lattice thermal stability, and the cerium-zirconium solid solution after strontium doping still strictly maintains the fluorite cubic structure, and it is not easy to precipitate metastable phase; strontium can give full play to the valence balance effect, promote the generation of oxygen vacancies, and improve the oxygen storage capacity.

[0027] (2) The dispersant is a mixture of gallic acid, lauric acid and stearylamine; the surfactant is a cationic surfactant, preferably dodecyldimethylbenzyl ammonium chloride, dodecylpyridinium ammonium chloride or hexadecyltrimethylammonium chloride:

[0028] Since the doping of multiple rare earth metals and alkaline earth metals may cause the crystal phase structure to change during the synthesis of cerium-zirconium solid solution, gallic acid can act as a bidentate ligand and form a chelate complex with the metal; the hydroxyl and carboxyl groups surround the rigid ring structure, restricting the free rotation of certain parts of the molecule and playing a semi-stereostabilizing role, thereby maintaining a specific stereo configuration. These characteristics can guide the synthesis of cerium-zirconium solid solution to a uniform cubic fluorite structure.

[0029] Stearylamine is composed of an amino terminal and a long-chain alkyl group. The amino terminal is a basic anchoring group, in which the nitrogen atom contains a lone pair of electrons and can accept hydrogen protons to form positively charged ammonium ions (-NH 3 + ) and conjugate base, due to CeO 2 -ZrO 2 The surface is weakly acidic, and ammonium ions will react with CeO 2 -ZrO 2 The formation of an electrostatic double layer further prevents CeO 2 -ZrO 2 The particles agglomerate to increase the specific surface area of ​​the cerium-zirconium solid solution; at the same time, the hexadecyl long-chain alkyl group at the other end has a moderate length and forms limited mutual entanglement in the solution, forming an ordered structure of a certain shape and size through the self-assembly effect, guiding the cerium-zirconium solid solution to arrange itself around the ordered structure and grow in a specific direction, thereby reducing the anisotropy of the cerium-zirconium solid solution, restricting the diffusion direction of oxygen vacancies, and improving the efficiency of oxygen vacancy migration.

[0030] The long-chain fatty acid part of lauric acid can electrostatically interact with the surface of the solid solution particles, which are alkaline as a whole, to form a thin adsorption layer. This adsorption layer can reduce the adhesion between the solid solution particles, making it easier to disperse the solid solution particles evenly during the preparation process.

[0031] The surfactant is a cationic surfactant (i.e., dodecyl dimethyl benzyl ammonium chloride, dodecyl pyridinium ammonium chloride or hexadecyl trimethyl ammonium chloride): During the coprecipitation process, tetravalent cerium ions and zirconium ions generate Ce(OH) 5 - and Zr(OH) 5 - The micelles formed by cationic surfactants are positively charged, and the ions attract each other. The ordered structure can easily adsorb on the surface of the micelles to form a microreactor, thereby making the metal ions evenly dispersed, which is beneficial to increase the specific surface area. DETAILED DESCRIPTION

[0032] The present invention is specifically described and illustrated below in conjunction with embodiments.

[0033] Example 1

[0034] Weigh 4 mol of cerium nitrate, 4 mol of zirconium oxynitrate, 0.5 mol of lanthanum nitrate, 0.5 mol of yttrium nitrate, 0.5 mol of strontium nitrate, 0.5 mol of magnesium nitrate, 1 mol of gallic acid, 1 mol of lauric acid and 8 mol of stearylamine for use.

[0035] Gallic acid, lauric acid and stearylamine are prepared into a dispersant for later use.

[0036] Add cerium nitrate, zirconium nitrate, lanthanum nitrate, yttrium nitrate, strontium nitrate and magnesium nitrate into 2.5L of water and stir until clear to prepare an aqueous solution; mix dodecyldimethylbenzylammonium chloride, n-hexanol and diethyl ether in a volume ratio of 1:1:3 to prepare 6L of surfactant solution, mix with the aqueous solution at room temperature to prepare a template solution for use.

[0037] Prepare a precipitant by adding 2L of 4.4mol / L ammonia water and a dispersant for later use.

[0038] The template liquid and the synthetic precipitant were mixed, stirred at a rate of 700 rad / min for 15 min, aged at 58°C for 1.5 h, and the pH value was monitored, and ammonia water was added as needed to maintain the system pH at 9.5-10.5.

[0039] The aged solution was placed in a centrifuge for centrifugal dispersion, and the obtained precipitate was washed with flowing ethanol until the conductivity of the precipitate was ≤30mS / cm. It was then placed in a muffle furnace and calcined at 850°C for 7.5h to obtain a modified cerium-zirconium solid solution.

[0040] Example 2

[0041] Weigh 5 mol of cerium nitrate, 3.5 mol of zirconium oxynitrate, 0.5 mol of neodymium nitrate, 0.4 mol of yttrium nitrate, 0.3 mol of strontium nitrate, 0.3 mol of magnesium nitrate, 0.8 mol of gallic acid, 0.8 mol of lauric acid and 7.9 mol of stearylamine for use.

[0042] Gallic acid, lauric acid and stearylamine are prepared into a dispersant for later use.

[0043] Cerium nitrate, zirconium oxynitrate, yttrium nitrate, neodymium nitrate, strontium nitrate and magnesium nitrate were added to 2.5 L of water and stirred until clear to prepare an aqueous solution; hexadecyltrimethylammonium chloride, n-hexanol and chloroform were mixed in a volume ratio of 1:1:5 to prepare 8 L of a surfactant solution, which was mixed with the aqueous solution at room temperature to prepare a template solution for use.

[0044] Add 2L of 5.1mol / L ammonia water and dispersant to prepare a precipitant for later use.

[0045] The template liquid and the synthetic precipitant were mixed, stirred at a rate of 800 rad / min for 10 min, aged at 65°C for 1 h, and the pH value was monitored, and ammonia water was added as needed to maintain the system pH at 9.5-10.5.

[0046] The aged solution was placed in a centrifuge for centrifugal dispersion, and the obtained precipitate was washed with flowing ethanol until the conductivity of the precipitate was ≤30mS / cm, and then placed in a muffle furnace and calcined at 900°C for 6h to obtain a modified cerium-zirconium solid solution.

[0047] Example 3

[0048] Weigh 4.5 mol of cerium nitrate, 3.5 mol of zirconium oxynitrate, 0.6 mol of praseodymium nitrate, 0.5 mol of lanthanum nitrate, 0.5 mol of strontium nitrate, 0.4 mol of magnesium nitrate, 2 mol of gallic acid, 2 mol of lauric acid and 4 mol of stearylamine for use.

[0049] Gallic acid, lauric acid and stearylamine are prepared into a dispersant for later use.

[0050] Add cerium nitrate, zirconium nitrate, praseodymium nitrate, lanthanum nitrate, strontium nitrate and magnesium nitrate into 2.5L of water and stir until clear to prepare an aqueous solution; mix dodecylpyridinium chloride, n-hexanol and acetone in a volume ratio of 1:1:4 to prepare 9L of surfactant solution, mix with the aqueous solution at room temperature to prepare a template solution for use.

[0051] Add 2L of 5.4mol / L ammonia water and dispersant to prepare a precipitant for later use.

[0052] The template liquid and the synthetic precipitant were mixed, stirred at a rate of 500 rad / min for 30 min, aged at 55°C for 2 h, and the pH value was monitored, and ammonia water was added as needed to maintain the system pH at 9.5-10.5.

[0053] The aged solution was placed in a centrifuge for centrifugal dispersion, and the obtained precipitate was washed with flowing ethanol until the conductivity of the precipitate was ≤30mS / cm, and then placed in a muffle furnace and calcined at 800°C for 8h to obtain a modified cerium-zirconium solid solution.

[0054] Comparative Example 1

[0055] Strontium nitrate and magnesium nitrate were replaced by cerous nitrate, and the remaining steps were the same as those in Example 1.

[0056] Comparative Example 2

[0057] Strontium nitrate was replaced by cerous nitrate, and only magnesium nitrate was used. The remaining steps were the same as those in Example 1.

[0058] Comparative Example 3

[0059] The magnesium nitrate was replaced by cerous nitrate, and only strontium nitrate was used. The remaining steps were the same as those in Example 1.

[0060] Comparative Example 4

[0061] The dispersant was replaced with aqueous ammonia, and the remaining steps were the same as in Example 1.

[0062] Comparative Example 5

[0063] Only gallic acid was used as the dispersant, and the total amount thereof remained unchanged. The remaining steps were the same as those in Example 1.

[0064] Comparative Example 6

[0065] The dispersant used was only stearylamine, the total amount of which remained unchanged, and the remaining steps were the same as in Example 1.

[0066] Comparative Example 7

[0067] No dodecyl dimethyl benzyl ammonium chloride was added to the surfactant solution, and dodecyl dimethyl benzyl ammonium chloride was replaced with an equal amount of n-hexanol. The remaining steps were the same as those in Example 1.

[0068] Test Example 1

[0069] Total oxygen storage capacity test: using H 2 -TPR method was used to test the oxygen storage capacity (OSC) of the modified cerium-zirconium solid solution. 100 mg of the modified cerium-zirconium solid solution was weighed and placed in a conical quartz tube reaction tube, which was connected to a thermal conductivity cell detector (TCD) and a chemical adsorption instrument (TPR mode). N was introduced at a rate of 25 mL / min. 2 , purified at 250°C for 40 min; then cooled to 65°C and introduced Ar / H 2 Mixed gas (H 2 The concentration was 8 vol%) and the chromatographic baseline was stabilized, and then the temperature was programmed to reduce the chromatographic baseline. The Ar / H 2 The mixed gas was heated from 65°C to 1000°C at a rate of 10°C / min and kept at this temperature for 50 min to obtain H 2 -TPR curve (abscissa is reduction temperature ℃; ordinate is hydrogen consumption rate), take 400℃, 450℃, 500℃, 600℃, 800℃ and 1000℃ respectively, calculate hydrogen consumption, and hydrogen consumption is obtained by peak area method. Repeat the above total oxygen storage capacity test using standard substance CuO with known oxygen storage capacity, and calculate the oxygen storage capacity of modified cerium-zirconium solid solution by comparing peak areas.

[0070]

[0071] It can be seen from Table 1 that the modified cerium-zirconium solid solutions prepared in Examples 1 to 3 of the present invention have a greater oxygen storage capacity at a temperature of 400 to 1000°C.

[0072] In addition, when the aging resistance test was carried out on Examples 1 to 3, the thermal conductivity of the samples was maintained at least 58m after calcination at 1100°C for 12 hours. 2 / g air specific surface area, at least 55m 2 / g of hydrothermal specific surface area and an oxygen storage capacity of no less than 1050 μmol / g, which meets the technical requirements of existing three-way catalysts.

[0073] Dynamic oxygen storage test: By simulating the periodic changes in the air-fuel ratio during engine operation, the oxygen storage / release performance of the modified cerium-zirconium solid solution is characterized, that is, the oxygen storage / release rate is characterized.

[0074] Weigh 100 mg of modified cerium-zirconium solid solution and place it in a conical quartz tube reaction tube. Connect O 2 Gas cylinder, CO cylinder and mass spectrometer. Set up a pulse program to periodically introduce CO and O 2 (CO inlet frequency was 0.1 Hz, maximum value was 22 mL / min, minimum value was 8 mL / min, and initial value was 10 mL / min; O 2 The frequency is 0.05 Hz, the maximum value is 11 mL / min, the minimum value is 4 mL / min, and the initial value is 11 mL / min. ), simulating the periodic change of the air-fuel ratio during engine operation, which leads to the change of exhaust gas composition.

[0075] First, O was introduced at 320 °C at 25 mL / min. 2 Purification 25min, N 2 Purge for 10 min; start the pulse program, raise the temperature to 1000°C, and introduce CO and O 2 , stop after 10 minutes; continue to cool down to 800℃, 600℃, 500℃, 450℃ and 400℃ respectively, repeat the above dynamic oxygen storage test steps, and finally keep warm for 40 minutes to detect the CO at the outlet of the conical quartz tube reaction tube. 2 The content of (μmol / g, g represents the mass of the modified cerium-zirconium solid solution) is used to characterize the oxygen storage / oxygen release performance of the modified cerium-zirconium solid solution. The specific test results are shown in Table 2.

[0076]

[0077] It can be seen from Table 2 that more CO is converted into CO in Examples 1 to 3. 2 , which means that in CO and O 2When periodically introduced, the modified cerium-zirconium solid solution in Examples 1 to 3 can fully capture oxygen when it is oxygen-rich, and can fully release oxygen when it is oxygen-poor, so that it participates in the oxidation reaction of CO.

[0078] Although the present invention is described in detail by way of embodiments, the present invention is not limited thereto. Without departing from the spirit and substance of the present invention, those skilled in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions should all be within the scope of the present invention.

Claims

1. A method for preparing a modified cerium-zirconium solid solution, characterized in that: Four types of metal salts, namely, cerium salt, zirconium salt, rare earth metal salt and alkaline earth metal salt, are added to a surfactant solution to prepare a template solution; ammonia water and a dispersant are used to prepare a precipitant; the template solution and the precipitant are stirred and aged, and the precipitate obtained after aging is washed and roasted to obtain a modified cerium-zirconium solid solution; The surfactant solution is prepared by mixing a surfactant, a surfactant auxiliary and an organic solvent, wherein the surfactant is one of dodecyl dimethyl benzyl ammonium chloride, dodecyl pyridinium ammonium chloride or hexadecyl trimethyl ammonium chloride; the surfactant auxiliary is n-hexanol; The dispersant is a mixture of gallic acid, lauric acid and stearylamine, and the molar ratio of gallic acid, lauric acid and stearylamine is 1:1:(2-10); the molar ratio of the dispersant to the total molar number of the four types of metal salts is (0.8-1):1; The rare earth metal salt is one or more of praseodymium nitrate, lanthanum nitrate, yttrium nitrate or neodymium nitrate; the alkaline earth metal salt is strontium nitrate and magnesium nitrate; based on the total molar number of the four types of metal salts as 100%, cerium salt accounts for 40-50%, zirconium salt accounts for 35-40%, rare earth metal salt accounts for 9-11%, and alkaline earth metal salt accounts for 6-10%; the molar ratio of strontium nitrate to magnesium nitrate is 1:(0.8-1).

2. The method for preparing the modified cerium-zirconium solid solution according to claim 1, characterized in that: The cerium salt is cerous nitrate; the zirconium salt is zirconyl nitrate.

3. The method for preparing the modified cerium-zirconium solid solution according to claim 2, characterized in that: Taking the total molar number of the four types of metal salts as 100%, cerium salt accounts for 40%, zirconium salt accounts for 40%, lanthanum nitrate accounts for 5%, yttrium nitrate accounts for 5%, strontium nitrate accounts for 5%, and magnesium nitrate accounts for 5%.

4. The method for preparing the modified cerium-zirconium solid solution according to claim 1, characterized in that: The organic solvent is one of chloroform, ether or acetone, and the volume ratio of the surfactant, the surfactant additive and the organic solvent is 1:1:(3~5).

5. The method for preparing the modified cerium-zirconium solid solution according to claim 1, characterized in that: The ratio of the added amount of four types of metal salts to the surfactant solution is 1: (0.6~0.9), where the four types of metal salts are the total molar number, measured in mol, and the surfactant solution is measured in L; the molar ratio of the total amount of cerium salt and zirconium salt to the added amount of ammonia water is 1: (1.1~1.35).

6. The method for preparing the modified cerium-zirconium solid solution according to claim 1, characterized in that: During aging, the pH is controlled at 9.5~10.5, the aging time is 1~2h, and the aging temperature is 55~65℃.

7. The method for preparing the modified cerium-zirconium solid solution according to claim 1, characterized in that: The stirring rate is 500~800rad / min; the conductivity of the precipitate after washing is ≤30mS / cm.

8. The method for preparing the modified cerium-zirconium solid solution according to claim 1, characterized in that: The calcination temperature is 800~900℃ and the calcination time is 6~8h.

Citation Information

Patent Citations

  • Preparation method of cerium-zirconium based solid solution

    CN104492414A

  • Composite ceria-zirconia solid solution and preparation method thereof

    CN105642269A

  • Preparation method for cerium-zirconium-aluminum-lanthanum-based oxygen storage material of mesoporous structure

    CN104525180A

  • Cerium-zirconium-based composite oxide, preparation method thereof and loaded automobile exhaust purification catalyst

    CN112827491A